High-flux ultrafast extreme-ultraviolet photoemission spectroscopy at 18.4 MHz pulse repetition rate - T. Saule (Nature Portfolio, 2019)
Space charge effects can distort the results of photoelectron spectroscopic measurements, and usually limit the allowable photon flux in an experiment. Here, the authors present an 18.4 MHz repetition rate high harmonic source in the 25–60 eV range, with a large count rate improvement over state-of-the-art attosecond setups under identical space charge conditions.